Implementasi Ruwatan dalam pernikahan di Tanah Jawa: Studi kasus di Desa Bedingin Kecamatan Sambit - Qulub, Ahmad Alfin Syifaul (Maliki Interdisciplinary Journal, 2023)
Javanese is one of the largest ethnic groups in Indonesia. The tribe has many different traditions and cultures. Javanese people are known as an area that is still closely related to belief in mystical things. The Javanese people have several theories that can be used as a basic basis for carrying out a ruwatan tradition. This tradition is believed to be able to prevent humans from various negative impacts caused by human activities themselves. This tradition in Javanese society is known as ruwatan. The purpose of this research is to find out the origins and the things that lie behind the ruwatan tradition in marriages that occur in Java. The results of this study illustrate that the origin of the existence of ruwatan begins with the existence of a wayang story in which there is a character named Batara Guru who has 2 wives, namely Pandemic and a concubine. From his wife named pandemic, Batara Guru was blessed with a son named Wisnu. Vishnu grows into a person of good character. The meaning of ruwatan in Javanese means free or detached. So that ruwatan can be interpreted as a request or request with all my heart so that they are free from all harm and always get protection from God Almighty.